Spatial Resilience of Outdoor Domestic Space in Mozambique - Veríssimo, Céline Felicio (TeMA - Journal of Land Use, Mobility and Environment, 2012)
Historically, the people of Mozambique have faced oppression and social spatial segregation and responded in a way that has reinforced rather than dismantled their traditional values. Since pre-colonial times, the population’s strategy for escaping from environmental and foreign political disruption has been to reinvent tradition, based on the principles of resilience, resistance and self-reliance. The development of decentralised human settlements, involving the appropriation of land for domestic space and the self-organisation of neighbourhoods, were strategies to protect communities from adversity and secure collective self-reliance. Following Mozambique’s conversion to globalization, the post-colonial ‘cement city’ is now the core of neo-liberalism, as a node of the global economy, where foreign donors and international market economy control national political economy, exacerbating the premise of the negation of self-sufficiency that continues to evolve resiliently at its margins. The adoption of a neo-liberal model of development during the 1990s, completely bypasses the realities of Mozambican society. This paper argues that the strategy of self-production of space regarding the household/Outdoor Domestic Space unit, which existed previously as a resistance strategy, first of all against colonialism and secondly, against the statist definition of socialism, thirdly, has become a successful strategy for survival, as the building block of the decentralised Agrocity, in the face of a global economy which totally neglects both the people and the land. Outdoor Domestic Space is a multifaceted space that refers to the external space surrounding the built house and which, in the case of Mozambique, is where daily life takes place, involving strong social, ecological and productive functions. Under successive periods of political economy oppression and environmental adversity, the Outdoor Domestic Space has been adapted and refined to ensure collective self-reliance. Shaping a green and ruralised urbanisation at the margins of the Mozambican post-colonial dualistic city, which I call the Agrocity, the Outdoor Domestic Space is resilient because it is able to adjust domestic space as a strategy to secure livelihoods, provide urban food, commerce and services, maintain vital kinship relationships and produce a comfortable and clean microclimate across the spontaneous neighbourhoods. This spatial resilience is the feature underlying the self-organisation of neighbourhoods with a new way of overcoming alienation from nature, which suggest the continuance of an innate relationship between society, the human habitat and nature.